2D to 3D Image Morphing Techniques - Patel, Arib; Shah, Rushabh; Karani, Ruhina (International Journal of Computer Sciences and Engineering, 2025)
This paper describes the techniques of image processing used for construction of 3D face models from a 2D input. 3D models play an important role in various fields. The advances in technologies have put a greater emphasis on efficient techniques of 2D to 3D conversion. 3D models can be developed manually or automatically. Automatic construction process faces certain problems such as identification of the subtle nuances present in the features of each individual. Also presenting a model which has the natural elements of each individual requires consideration. The process can be carried out in two phases; in the initial phase a 2D input is fed as input from which a new 3D model is registered by computing one-to-one correspondence to a 3D model present in a database of 3D models. Next the naturalness of the models is taken into consideration and the unlikely appearance factor is minimized. This paper discusses about the different techniques used in 2D to 3D conversion, how well they have contributed in increasing the efficiency of the process and what future research needs to be conducted.